FLUORIDE LEVELS OF DRINKING WATER AND DFZNTAL CARIES IN HAZARA AND MIANWALI - Khan, Shaheen Pervez; Khan, Jahangir; Waheed, Abdul (Journal of Ayub Medical College Abbottabad, 1995)
Two hundred and sixteen drinking water samples from various sources in Hazara Division and District Mianwali were tested for fluoride levels. In Hazara Division, out of 161 water samples, only 4 samples were found to ha\’e fluoride levels within acceptable range (0.8-1.5 PPM), remaining samples had fluoride either very low or not at all. The fluoride range was from 0.0 to 0.9 ppm with a mean of 0.11 ppm. In District Mianwali, 55 drinking water samples were tested, the fluoride content was within normal limits or high, except few samples having less fluoride concentration. The range was 0.3 to 6.5 ppm with mean of 1.46 ppm. 1739 Primary and High School going boys and girls of District Abbottabad, Haripur and Mianwali were examined for dental caries. In Hazara Division 61 % were found to have mild to severe dental caries while in District Mianwali, it was 4.9% while mottling was 14.6%.